2014
DOI: 10.1186/1471-2458-14-1190
|View full text |Cite
|
Sign up to set email alerts
|

Namibia’s path toward malaria elimination: a case study of malaria strategies and costs along the northern border

Abstract: BackgroundLow malaria transmission in Namibia suggests that elimination is possible, but the risk of imported malaria from Angola remains a challenge. This case study reviews the early transition of a program shift from malaria control to elimination in three northern regions of Namibia that comprise the Trans-Kunene Malaria Initiative (TKMI): Kunene, Omusati, and Ohangwena.MethodsThirty-four key informant interviews were conducted and epidemiological and intervention data were assembled for 1995 to 2013. Mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 20 publications
0
71
0
Order By: Relevance
“…In the Philippines declining marginal expenditures were observed from control to POR, where costs per PAR were more than halved [57]. Similar findings have been reported in three Namibian regions in a recent study published after the initial search was conducted [78]. In contrast, Ruberu’s analysis in Sri Lanka suggested that the high short-term cost of elimination is exceeded by long-term investments in control and the resulting consequences of productivity losses [46].…”
Section: Discussionmentioning
confidence: 56%
“…In the Philippines declining marginal expenditures were observed from control to POR, where costs per PAR were more than halved [57]. Similar findings have been reported in three Namibian regions in a recent study published after the initial search was conducted [78]. In contrast, Ruberu’s analysis in Sri Lanka suggested that the high short-term cost of elimination is exceeded by long-term investments in control and the resulting consequences of productivity losses [46].…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, access to health facilities and malaria preventive measures are thought to be poor at most health facilities in Angola. 9 This underscores the need for neighbouring countries to work together to implement malaria control activities.…”
Section: Discussionmentioning
confidence: 99%
“…23 Similarly in Namibia, the highest risk of malaria was found along the border with Angola, which is considered malaria endemic. 24,25 The increased risk of malaria transmission along international borders has been attributed to poorer access to health care, differences in malaria endemicity, the porosity of borders, frequent human population movement, and suitable climatic conditions for malaria transmission. 26 Interestingly, proximity to a health facility was not associated with malaria.…”
Section: Discussionmentioning
confidence: 99%
“…29 The movement of parasite-carrying individuals from the higher transmission setting of Mozambique may be undermining malaria control in eastern Zimbabwe, as suggested by studies in other countries where malaria resurgence has been attributed in part to frequent human population movement across international borders. 24,30 Regionally, several intercountry collaborations have been developed to address cross-border malaria, including the Lubombo Spatial Development Initiative between Mozambique, South Africa, and Swaziland, 31 the Trans-Kunene Malaria Initiative between Namibia and Angola, 25 and the Trans-Zambezi Malaria Initiative between Angola, Botswana, Namibia, Zambia, and Zimbabwe. 24 The success of these regional initiatives has been hampered, however, by lack of political will, limited funding, slow mobilization of resources, and poor coordination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation